Impact of Foreign Bank Presence on Domestic Banking Efficiency: An Institutional Perspective from Uzbekistan - Gofirjonov Khabibullokh Nozim Ugli; Ida Farida Adi Prawira; Rika Nurrizkiana; Qudratov Inomjon Nemat Ugli (MARAS : Jurnal Penelitian Multidisiplin, 2026)
This study examines the impact of foreign bank presence on domestic banking efficiency through an 18-year longitudinal case study of KDB Bank Uzbekistan between 2006 and 2024. Framed by institutional theory, particularly the Burns and Scapens process model and the concept of institutional isomorphism, the study investigates how foreign bank entry influences competition, operational efficiency, technology diffusion, and organizational change in the Uzbek banking sector. The research adopts a mixed-methods sequential explanatory design that combines financial statement analysis, Data Envelopment Analysis (DEA), Stochastic Frontier Analysis (SFA), difference-in-differences estimation, 22 semi-structured interviews, a survey of 156 banking professionals, and documentary analysis. The findings indicate that foreign bank entry contributed to lower market concentration, improved domestic cost efficiency, wider adoption of digital banking infrastructure, and stronger risk-management practices. In particular, lower cost-to-income ratios among comparable domestic banks indicate an efficiency gain rather than deterioration. The study also shows that spillover effects operated through competition, staff mobility, benchmarking, and regulatory learning. Theoretically, the article extends institutional explanations of banking change in an emerging market setting. Practically, it offers evidence relevant to policymakers designing foreign bank entry strategies that both encourage modernization and protect balanced domestic banking development.